Black garlic: transformation effects, characterization and consumer purchase intention - Resende Nassur, Rita de Cássia Mirela; Vilas Boas, Eduardo Valério de Barros; Resende, Francisco Vilela (Comunicata Scientiae, 2018)
Black garlic is produced from chemical and biochemical reactions when the fresh garlic bulb is submitted to specific temperature and moisture conditions. The aim of this study was to evaluate quality and nutritional changes on bulbs before and after the transformation in black garlic, presenting the new product for the consumer, evaluating the purchase intention. Commercial garlic bulbs cv. Amarante were obtained and transformed in black garlic. The color, proximate composition (moisture, crude lipid, crude protein, crude fiber, ash and nitrogen-free extract), total sugars, total phenolics content and antioxidant activity were evaluated on fresh and black garlic bulbs. The transformation of garlic in black garlic resulted in an increase on crude lipid, crude protein, total sugars, antioxidant activity and total phenolic content. A multivariate analysis was performed and the characteristics of nutritional interest were positively related to the black garlic samples and a completely separation of the products before and after processing can be observed, affirming the physical, chemical, nutritional and sensory attributes difference. Only 20% of the surveyed consumers affirmed that they already knew the product and 55% classified the product after visual evaluation between “liked slightly” and “liked very much”, with 62% of purchase intention by the interviewed consumers.